MODERN REQUIREMENTS OF PRIMARY SCHOOL EDUCATION - Turgunbaeva Tozhigul (Western European Studies, 2024)
The modern world requires teachers to use advanced pedagogical and new information technologies in the educational process. The organization of the educational process in primary school using modern technologies and the formation of basic competencies in primary school students is becoming increasingly relevant.
Keywords: primary school; primary education; technology